Microsatellite (mEgCIR3808) analysis in oil palm: an optimisation of a direct PCR-based using FTA card as a storage medium - Mohd Asri, Nurul Ain Shahira; Zulkifli, Amirul Akmal; Midin, Mohd Razik; Wan Hanafi, Wan Nurhayati (Penerbit UTHM, 2024)
This paper explores the effectiveness of Flinders Technology Associates(FTA) card, with a focus on the role of FTA card application in storing oil palm DNA for PCR analysis. The study underscores the importance of optimising the washing steps of FTA card and validation of PCR amplification of using optimised washing steps towards oil palm leaves. Therefore, the study specifically examines practices for FTA washing method for oil palm sample which is crucial and necessary in obtaining promising results. The optimised washing steps such adding centrifugation while washing the FTA cards matters and has proven to enhance the band intensity of the PCR amplification results. An optimised, proper and accurate first-basis fundamental steps will contribute the value of SSR fingerprinting as a molecular detection for Elaeis guineensis, highlighting the potential of genetic markers in oil palm research.